Effects of chlorine exposure on physiochemical properties and performance of polyamide membranes - Do, Thanh Van (2013)
In nanofiltration (NF) and reverse osmosis (RO) processes, membranes are prone to biofouling and need to be cleaned periodically using oxidizing biocides, including the most widely used chlorine in different forms. The polyamide-based (PA) separation layer of thin film composite (TFC) membranes can be modified or degraded during contact with those agents. Understanding the effects of chlorine exposure on PA membranes is essential to improving the life span of membranes from both manufacturing and operation perspectives. This research presents a systematic investigation of the effects of chlorine exposure on the physiochemical properties and performance of PA membranes. To study the degradation of PA NF and RO membranes by sodium hypochlorite, six coated and uncoated fully aromatic (FA) and piperazine (PIP) semi-aromatic PA membranes were treated with hypochlorite solution and analyzed by X-ray photoelectron spectroscopy (XPS) and attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy. XPS results showed that in chlorine treated FA PA membranes the ratio of bound chlorine to surface nitrogen was 1:1 whereas it was only 1:6 in the case of PIP PA membranes. The surface oxygen of uncoated FA and PIP membranes increased with increasing hypochlorite concentration whereas it decreased for coated FA membranes. High resolution XPS data supported that chlorination increased the number of carboxylic groups on the PA surface, which appeared to form by hydrolysis of the amide bonds (C(O)–N). FTIR data indicated the disappearance of the amide II band (1541 cm-1) and aromatic amide peak (1609 cm-1) in both coated and uncoated chlorinated FA membranes, consistent with the N-chlorination suggested by the XPS results. Furthermore, the surface charge of the chlorinated membranes at low pH (< 6) became negative, consistent with amide-nitrogen chlorination. Chlorination appeared to either increase or decrease membrane hydrophobicity depending on the chlorination exposure conditions, which implied that N-chlorination and hydrolysis may be competing processes. The effects of property changes on the performance were also observed for the NF90, BW30 and NF270 membranes. Detailed appraisal of NF and RO membrane performance due to chlorine treatment was carried out by exposing three PA-TFC membranes (NF90, BW30 and NF270) to different concentrations of sodium hypochlorite (NaOCl) at pH 5 for 24 h. The elemental composition obtained from XPS showed that the chlorine content in the PA layer increased with the chlorine concentration. Treatment of membranes with 10 ppm Cl increased the membrane hydrophilicity. In contrast, when treated with 1000 ppm Cl or more, the membranes became less hydrophilic. Water permeability values for all three membrane types declined with increased chlorine concentrations. Filtration of polyethylene glycols (PEGs) with molecular weights of 200, 400 and 600 Daltons (Da) was performed to investigate the influence of chlorine treatment on the membrane molecular weight cut-off (MWCO) and rejection by size exclusion. Treatment with 10 and 100 ppm Cl lowered the MWCO while treatment with higher concentrations increased the MWCO. All chlorinated membranes experienced higher NaCl rejection compared to the virgin ones. The performance of NF90 was tested with respect to the rejection of inorganic contaminants including boric acid (H3BO3) and arsenic (H2AsO4-). The boron rejection results paralleled the PEG rejection, whereas those for arsenic followed the NaCl rejection patterns. The changes in membrane performance due to chlorine treatment were explained in terms of competing mechanisms: membrane tightening, bond cleavage by N-chlorination and chlorination promoted polyamide hydrolysis. The effects of chlorine exposure conditions on the physiochemical properties and performance of a polyamide membrane were studied by treating an NF90 membrane with sodium hypochlorite at different concentrations, pH and duration. The changes in membrane elemental composition and bonding chemistry obtained from XPS and ATR-FTIR revealed the impacts of two competing mechanisms: N-chlorination and chlorination promoted hydrolysis. More chlorine was incorporated into the PA matrix at pH < 7, at which HOCl is dominant; while chlorine promoted hydrolysis was more favorable at pH > 7 with an abundance of hydroxyl groups. The membrane surface became more hydrophobic when chlorination was dominant, which in turn caused the water permeability of the chlorinated membrane to decrease. Meanwhile, the membrane became more hydrophilic and less cross-linked when hydrolysis effects were governing, which made the membrane more permeable for water. Rejection of charged solutes (NaCl, As(V)) improved under most chlorinating conditions due to increased charge density. However, when hydrolysis was severe (≥ 1000 ppm, pH 7 and 9), the enhanced charge repulsion effect could not compensate for the extensive amide bond cleavage, resulting in decreased rejection. The lower rejection of neutral boric acid provided strong evidence of a less cross-linked separation layer.